Acyl modifications in bovine, porcine, and equine ghrelins - Ida, Takanori; Tominaga, Hatsumi; Iwamoto, Eri; Kurogi, Akito; Okura, Ayaka; Shimada, Kengo; Kato, Johji; Kuwano, Atsutoshi; Ode, Hirotaka; Nagata, Sayaka; Kitamura, Kazuo; Yazawa, Takashi; et al. (Frontiers in Endocrinology, 2024)
Ghrelin is a peptide hormone with various important physiological functions. The unique feature of ghrelin is its serine 3 acyl-modification, which is essential for ghrelin activity. The major form of ghrelin is modified with n-octanoic acid (C8:0) by ghrelin O-acyltransferase. Various acyl modifications have been reported in different species. However, the underlying mechanism by which ghrelin is modified with various fatty acids remains to be elucidated. Herein, we report the purification of bovine, porcine, and equine ghrelins. The major active form of bovine ghrelin was a 27-amino acid peptide with an n-octanoyl (C8:0) modification at Ser3. The major active form of porcine and equine ghrelin was a 28-amino acid peptide. However, porcine ghrelin was modified with n-octanol (C8:0), whereas equine ghrelin was modified with n-butanol (C4:0) at Ser3. This study indicates the existence of structural divergence in ghrelin and suggests that it is necessary to measure the minor and major forms of ghrelin to fully understand its physiology.